Increasing antibiotic resistance amongst Uropathogenic E. coli isolated from inpatients with symptomatic UTI - a three year study - Dr. Yogita Verma; Dr. Krunal Shah; S. S. Hemachander (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Escherichia coli (E.coli) is one of the most common uropathogen worldwide. In the past few years, uropathogenic E.coli has become increasingly resistant to many drugs.Materials and Methods: This prospective observational study was conducted from January 2014 to December 2016. Semiquantitative urine culture was done on blood agar and MacConkey agar using standard technique. Cultures showing a significant growth of 105 CFU/ml or more were further processed. Identification and analysis of antibiotic susceptibility patterns was done by VITEK®2 (bioMerieux, USA).Results: A total of 674 E. coli samples were included in the final analysis. The isolates showed highest overall sensitivity to imipenem (75.82%) and nitrofurantoin (72.25%) whereas highest resistance was observed in case of amoxicillin-clavulinic acid (84.12%) and cephalosporins (71.96-83.23%), followed by ciprofloxacin (72.70%), amikacin (64.39%) and TMP-SMX (64.24%). Over three years duration, a trend of increasing resistance was observed in the case of cephalosporins, ciprofloxacin and trimethoprim-sulfamethoxazole (TMP-SMX). Percentage of MDR E.coli also increased over three years.Conclusion: There is an increase in antibiotic resistance amongst uropathogenic Escherichia coli over the past three years. Routine surveillance of resistance patterns should continue in the hospitals and antibiotic policy should be constantly updated. Judicious use of antibiotics is the need of the hour.